2011
DOI: 10.1007/s00277-011-1289-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic characterization of adult T-cell acute lymphoblastic leukemia with del(9)(q34);SET-NUP214 rearrangement

Abstract: SET-NUP214 rearrangement is a recently recognized recurrent chromosomal translocation mostly observed in T-ALL. In order to characterize this rare entity, we performed phenotypic and genetic characterization of SET-NUP214 rearrangement through an investigation of a series of 40 consecutive samples of adult T-ALL that was selected among 229 adult ALL cases during 4 years in a single institution. Four cases (10%) of SET-NUP214 translocation were identified in our study. In all cases, diagnosis of T-ALL was estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…The majority of these patients experienced T-ALL (38/42; 90.4%), while other subtypes of leukemia accounted for <10%, including AUL (4.8%), AML (2.4%) and B-ALL (2.4%). Ben Abdelali et al (12) reported an incidence of SET-NUP214 of ~5.6% among 196 patients with T-ALL, which was slightly lower than that reported by previous studies in China and Korea concerning 59 (10.3%) and 40 (10.0%) patients with T-ALL, respectively (8,10). According to previous studies, the incidence of SET-NUP214 among patients with T-ALL appears to be ~3.0-10.3% (3,4,7,8,10,12).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The majority of these patients experienced T-ALL (38/42; 90.4%), while other subtypes of leukemia accounted for <10%, including AUL (4.8%), AML (2.4%) and B-ALL (2.4%). Ben Abdelali et al (12) reported an incidence of SET-NUP214 of ~5.6% among 196 patients with T-ALL, which was slightly lower than that reported by previous studies in China and Korea concerning 59 (10.3%) and 40 (10.0%) patients with T-ALL, respectively (8,10). According to previous studies, the incidence of SET-NUP214 among patients with T-ALL appears to be ~3.0-10.3% (3,4,7,8,10,12).…”
Section: Discussionmentioning
confidence: 80%
“…The SET-NUP214 fusion gene has been previously reported in T-ALL, but rarely in AML and AUL (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, it has not been be reported thus far in B-ALL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations